Pengembangan Literasi Energi Terbarukan Melalui Edukasi Teknologi PLTS pada Siswa MTS Negeri 1 Mataram - Sultan, Sultan; Muljono, Agung B; Nrartha, I Made Ari; Yadnya, Made Sutha; Ginarsa, I Made; Sasongko, Sudi Maryanto Al; Widianty, Desi (Jurnal Gema Ngabdi, 2024)
Renewable energy knowledge continues to be implemented by the University of Mataram. Community service activities, especially segmentation of the younger generation, are concentrated in Madrasah Tsanawiyah (MTs). This activity plays an important role in increasing the awareness of the younger generation about sustainable energy and environmentally friendly technology. The community service carried out at MTs Negeri 1 Mataram aims to increase students' understanding of renewable energy, especially solar energy, through interactive socialization and education activities. The evaluation of the results of the activity using pre-test and post-test showed a significant increase in student knowledge. The average pre-test score of 68.20 increased to 85.75 after participating in the education program, reflecting the effectiveness of the approach used. These results confirm the importance of integrating materials on renewable energy in the school curriculum, so that students can understand and actively contribute to maintaining environmental sustainability in the future.